Preparation method of enzyme coupling catalyst regulated and controlled by near-infrared second-region light
By growing copper chalcogenide quantum dots in situ on natural enzymes, and using their local surface plasmon resonance effect, the near-infrared two-zone light regulation of enzyme activity is achieved, and the problem of insignificant coupling effect of photoenzymes in the prior art is solved, and more efficient catalytic effect and better tissue permeability are achieved.
Patent Information
- Application Number
- CN202510027595.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
AI Technical Summary
The prior art cannot effectively utilize near-infrared two-zone light to regulate enzyme activity, and the particle size of the enzyme-modified material is large, and the penetration of the light source material and tissue is limited, resulting in insignificant catalytic effect.
By growing copper chalcogen compound quantum dots in situ on natural enzymes, the local surface plasmon resonance effect of copper chalcogen nanoparticles can achieve near-infrared two-zone light regulation of enzyme activity.
Photoenzyme coupling at a microscopic angle is achieved, the regulation accuracy and efficiency of enzyme activity is improved, the catalytic effect is enhanced, and the permeability of materials and tissues is higher due to the use of near-infrared two-zone light.
Smart Images

Figure CN119823970A_ABST
Abstract
Description
[Technical field]
[0001] The invention belongs to the technical field of catalyst preparation, and particularly relates to a method for preparing an enzyme coupling catalyst regulated by near-infrared second-region light. [Background technology]
[0002] The above effects can be achieved by designing or modifying natural enzymes. It can also change the enzyme's selectivity for substrates, improve enzyme reaction kinetic parameters, and enable natural enzymes to retain greater activity under some extreme conditions.
[0003] At present, people have designed a photoenzyme coupling system that combines natural enzymes with external light regulation. The principle is to modify the enzyme by selecting nanomaterials with inherent photothermal effect, thus making it a bridge between enzyme catalysis and photochemistry. When irradiated with light of corresponding wavelength, these nanomaterials with photothermal effect can achieve local heating, thereby achieving regulation of enzyme activity. Studies have shown that after natural enzymes are modified by the attachment of ultra-small nanoparticles, the enzymes can maintain better enzyme activity and can reduce or prevent unnecessary interactions between enzyme molecules. When the size of the natural enzyme is smaller than the size of the attached carrier (including polymers, nanoparticles, nanorods and nanoflowers), the nanomaterial must introduce covalent bonds through surface functionalization to modify the enzyme, which usually leads to a significant decrease in enzyme activity and damage to light regulation.
[0004] At present, the existing technology has synthesized ultra-small platinum nanoparticles (PtNP) located inside the enzyme. The particles are locally heated by the photothermal effect under the irradiation of 808nm light in the near-infrared region 1, and the activity of the enzyme embedded in the PtNP (E-Pt) is significantly enhanced, thereby using light control to regulate the enzyme activity. The process can also be finely controlled by adjusting the irradiation time and laser power density.
[0005] However, the above-mentioned light control adjustment range is mainly the mature visible light to near infrared region I (NIR-I, 400-900 nanometers) light source, while the near infrared region II light in the "second near infrared window" (NIR-II) at 1000-1700 nanometers, which has higher penetration and lower damage to the human body, has attracted great attention. Recent studies have shown that in the NIR-II region, the attenuation, scattering and background autofluorescence of light are all reduced. Because NIR-II has high deep tissue penetration and spatial resolution, it can be used in a wider range of biological applications with unprecedented low attenuation and scattering rates. At present, there is no relevant literature reporting the use of near infrared region II light for photoenzyme coupling. [Summary of the invention]
[0006] In view of the above, it is necessary to provide a method for preparing an enzyme-coupled catalyst regulated by near-infrared light in the second region to solve the problems in the prior art of being unable to microscopically regulate enzyme activity, large particle size of enzyme-modified materials, limited penetration of light source materials and tissues, and significant catalytic effect of the enzyme cascade system.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing an enzyme-coupled catalyst regulated by near-infrared light in the second region, the method comprising the following steps:
[0009] (1) dispersing the natural enzyme in ultrapure water to obtain an enzyme solution for later use;
[0010] (2) After the CuCl2 solution is added to the enzyme solution, ultrapure water is added, followed by stirring to uniformly disperse the copper source in the enzyme solution to obtain a mixed system for standby use;
[0011] (3) The sodium borohydride solution and the sulfide salt solution are fully mixed and reacted vigorously and fully. When the color of the reaction system becomes transparent, a reaction solution A is obtained and set aside;
[0012] (4) adding the reaction solution A of step (3) to the mixed system of step (4) and mixing thoroughly, the reaction system rapidly changes from transparent and colorless to reddish brown, and the reaction system gradually changes from reddish brown to dark green, the reaction is complete, and a reaction solution B is obtained for standby use;
[0013] (5) transferring the reaction solution B into a dialysis bag and purifying the reaction solution B;
[0014] (6) After purification, the reaction solution B was transferred to a freeze dryer for freeze drying to obtain a dry dark green sample powder. The sample powder was stored in a refrigerator at -85 to -75°C for later use.
[0015] In the present invention, further, in the step (1), the material-liquid ratio of the natural enzyme to ultrapure water is 8-12 mg: 1 mL.
[0016] In the present invention, further, the concentration of the CuCl2 solution in step (2) is 0.01-0.03M, the amount of ultrapure water added accounts for 30-40% of the amount of ultrapure water in step (1), and the stirring speed is 850-950rpm.
[0017] In the present invention, further, the concentration of the sodium borohydride solution in step (3) is 0.5-0.7M, and the concentration of the sulfide salt solution is 0.08-0.12M.
[0018] In the present invention, further, the molecular weight cutoff value of the dialysis bag in step (5) is 3200-3700Da, and the purification is specifically to transfer the solution to the dialysis bag and then dialyze it 10 times with deionized water to remove excess impurities and ions in the solution.
[0019] In the present invention, further, the natural enzyme is one of a hydrolase, a protease or an oxidoreductase.
[0020] In the present invention, further, the chalcogenide salt solution is a solution prepared by configuring oxides and salts of relevant chalcogenide elements.
[0021] The catalyst of the present application is suitable as an optical regulation material for phototherapy.
[0022] The present invention has the following beneficial effects:
[0023] 1. The present invention proposes a nanozyme-natural enzyme coupling catalyst regulated by near-infrared light in the second region. Specifically, by in situ growing copper sulfide quantum dots on the natural enzyme and utilizing the LSPR effect of copper sulfide nanoparticles, photoenzyme coupling at a microscopic perspective is achieved.
[0024] 2. The present invention uses near-infrared light in the second region to regulate enzyme activity, which has higher material and tissue permeability. When irradiated with laser in the second region of the near-infrared, the nanoparticles used have strong absorption capacity in the second region of the near-infrared and are catalysts with nanozyme properties. These nanoparticles can more effectively absorb light energy to produce localized surface plasmon effects, and the related physical phenomena produced by this effect can further promote the catalytic effect of nanozymes. The present invention is applicable to the optical regulation of enzyme cascade systems of all natural enzymes and nanozymes. The coupling of nanozymes and natural enzymes can further design the enzyme cascade system to further enhance the catalytic effect. At the same time, combined with the regulation performance of near-infrared optics, the activity of the composite catalyst can be remotely regulated, which has universal application.
Brief Description of the Drawings
[0025] Figure 1 This is a graph of UV absorption comparison data;
[0026] Figure 2 This is a photothermal comparison data chart;
[0027] Figure 3 Data graph for photothermal regulation to enhance enzyme activity;
[0028] Figure 4 This is a transmission electron microscopy image of the enzyme composite catalyst after modification of the material. [Specific implementation method]
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific implementation disclosed below.
[0030] Embodiment 1:
[0031] This embodiment provides a method for preparing an enzyme coupling catalyst regulated by near-infrared light in the second region, the method comprising the following steps:
[0032] (1) Disperse 8 mg of natural enzyme in 1 mL of ultrapure water to obtain an enzyme solution for later use;
[0033] (2) After adding a 0.01 M CuCl2 solution to the enzyme solution, 0.30 mL of ultrapure water was added, and then stirred at a stirring speed of 850 rpm to uniformly disperse the copper source in the enzyme solution to obtain a mixed system for standby use; the enzyme solution is a protease;
[0034] (3) A 0.5M sodium borohydride (NaBH4) solution and a 0.08M sodium sulfite solution were fully mixed, the solution was fully reduced, and the reaction was intensely and fully carried out for about 10 minutes. When the color of the reaction system turned transparent, a reaction solution A was obtained and set aside;
[0035] (4) taking 80 μL of the reaction solution A of step (3) and adding it to the mixed system of step (4) and mixing thoroughly to fully mix the copper source and the selenium source, the reaction system quickly changes from transparent and colorless to reddish brown, and after about 2 hours, the reaction system gradually changes from reddish brown to dark green, and the copper sulfide compound is successfully synthesized and the reaction is completed, and a reaction solution B is obtained for standby use;
[0036] (5) transferring the reaction solution B to a dialysis bag (molecular weight cutoff value is 3200Da) and purifying the reaction solution B; specifically, after the solution is transferred to the dialysis bag, it is dialyzed 10 times with deionized water to remove excess impurities and ions in the solution;
[0037] (6) After purification, the reaction solution B was transferred to a freeze dryer for freeze drying to obtain a dry dark green fine sample powder. The sample powder was stored in a refrigerator at -75°C for standby use. The dark green sample powder was the catalyst prepared as described above.
[0038] Embodiment 2:
[0039] This embodiment provides a method for preparing an enzyme-coupled catalyst regulated by near-infrared light in the second region, the method comprising the following steps:
[0040] (1) Disperse 10 mg of natural enzyme in 1 mL of ultrapure water to obtain an enzyme solution for later use;
[0041] (2) After adding a 0.02M CuCl2 solution to the enzyme solution, 0.35mL of ultrapure water was added, and then stirred at a stirring speed of 900rpm to uniformly disperse the copper source in the enzyme solution to obtain a mixed system for standby use; the enzyme solution is a hydrolase;
[0042] (3) A sodium borohydride (NaBH4) solution with a concentration of 0.6 M and a selenium dioxide solution with a concentration of 0.1 M are fully mixed, the solution is fully reduced, and the reaction is intensely and fully reacted for about 10 minutes. When the color of the reaction system becomes transparent, a reaction solution A is obtained and set aside;
[0043] (4) taking 100 μL of the reaction solution A of step (3) and adding it to the mixed system of step (4) and mixing thoroughly to fully mix the copper source and the selenium source, the reaction system quickly changes from transparent and colorless to reddish brown, and after about 2 hours, the reaction system gradually changes from reddish brown to dark green, and the copper sulfide compound is successfully synthesized and the reaction is completed, and a reaction solution B is obtained for standby use;
[0044] (5) transferring the reaction solution B to a dialysis bag (molecular weight cutoff value is 3500Da) and purifying the reaction solution B; specifically, after the solution is transferred to the dialysis bag, it is dialyzed 10 times with deionized water to remove excess impurities and ions in the solution;
[0045] (6) After purification, the reaction solution B was transferred to a freeze dryer for freeze drying to obtain a dry dark green fine sample powder. The sample powder was placed in a refrigerator at -80°C for storage until use. The dark green sample powder was the catalyst prepared as described above.
[0046] Embodiment 3:
[0047] This embodiment provides a method for preparing an enzyme-coupled catalyst regulated by near-infrared light in the second region, the method comprising the following steps:
[0048] (1) Disperse 12 mg of natural enzyme in 1 mL of ultrapure water to obtain an enzyme solution for later use;
[0049] (2) After adding a 0.03M CuCl2 solution to the enzyme solution, 0.40 mL of ultrapure water was added, and then stirred at a stirring speed of 950 rpm to uniformly disperse the copper source in the enzyme solution to obtain a mixed system for standby use; the enzyme solution is a redox enzyme;
[0050] (3) A sodium borohydride (NaBH4) solution with a concentration of 0.7 M and a sodium tellurite solution with a concentration of 0.12 M are fully mixed, the solution is fully reduced, and the reaction is intensely and fully carried out for about 10 minutes. When the color of the reaction system becomes transparent, a reaction solution A is obtained and set aside;
[0051] (4) taking 120 μL of the reaction solution A of step (3) and adding it to the mixed system of step (4) and mixing thoroughly to fully mix the copper source and the selenium source, the reaction system quickly changes from transparent and colorless to reddish brown, and after about 2 hours, the reaction system gradually changes from reddish brown to dark green, and the copper sulfide compound is successfully synthesized and the reaction is completed, and a reaction solution B is obtained for standby use;
[0052] (5) transferring the reaction solution B to a dialysis bag (molecular weight cutoff value is 3700Da) and purifying the reaction solution B; the purification is specifically to dialyze the solution 10 times with deionized water after the solution is transferred to the dialysis bag to remove excess impurities and ions in the solution;
[0053] (6) After purification, the reaction solution B was transferred to a freeze dryer for freeze drying to obtain a dry dark green fine sample powder. The sample powder was placed in a refrigerator at -85°C for storage until use. The dark green sample powder was the catalyst prepared as described above.
[0054] Test example:
[0055] In order to illustrate the practical value of this application, the applicants conducted comparative tests in groups:
[0056] Specifically divided into:
[0057] Group 1: PAP;
[0058] Group 2: A PAP-Cu2Se composite catalyst prepared by the method of Example 2, wherein the natural enzyme of Example 2 is PAP.
[0059] The UV absorption, photothermal data, and photothermal regulation-enhanced enzyme activity values of the above groups of products were compared, and the results were as follows: Figure 1-3 As shown;
[0060] in, Figure 1 It is the ultraviolet absorption comparison diagram of two groups, and it can be seen from the figure that the ultraviolet-visible spectrum comparison in the wavelength range of 600 to 1400nm. In this spectral range, papain does not show any significant absorption peak, which shows that papain itself does not absorb ultraviolet-visible light in the detection wavelength range.
[0061] In contrast, the spectrum of the composite pap-Cu2Se shows a distinct absorption edge near 1400 nm. This phenomenon may be attributed to the localized surface plasmon resonance (LSPR) effect, which is a collective oscillation phenomenon of metal nanoparticles that strongly absorb and scatter light at specific wavelengths.
[0062] In this study, the absorption edge of the pap-Cu2Se composite at around 1400nm indicated that cuprous selenide (Cu2Se) nanoparticles were successfully synthesized on the surface of papain. This conclusion is based on the LSPR effect of cuprous selenide nanoparticles in the near-infrared region, which is reflected in the spectrum of the composite. Through this absorption feature, the presence of cuprous selenide nanoparticles can be inferred and their synthesis on papain can be further confirmed.
[0063] Figure 2 The two sets of light-thermal comparison data are shown in Figure 2. Figure 2 It can be seen from the experimental data that at 1.0W / cm 2 Under the irradiation of laser power density, the solution temperature of pap-Cu2Se aqueous dispersion increased significantly from 23.5℃ to 30℃, indicating that the composite material has efficient photothermal conversion ability. Relatively speaking, the temperature change of pure papain aqueous dispersion with the same concentration was not significant under the same laser power density. This comparison result further confirms the superiority of pap-Cu2Se composite material in photothermal conversion efficiency compared with pure papain aqueous dispersion.
[0064] Figure 3 This is a comparison chart of the two groups' data on photothermal regulation to enhance enzyme activity. Figure 3 It can be seen that in the experiment of laser enhancement of enzyme activity, we compared the changes in peroxidase activity of the pap control group and the pap-Cu2Se experimental group under different laser power conditions. The experimental results revealed that laser irradiation has a significant enhancement effect on enzyme activity, especially in the pap-Cu2Se composite material. Specifically, at 1W / cm 2 Under the condition of laser power of 1W W / cm2, no significant increase in peroxidase activity was observed in the pap control group, which may indicate that the activity of pure papain remained in a relatively stable state without laser stimulation. However, when the pap-Cu2Se experimental group was introduced, the situation changed significantly. 2 Under the laser power condition, the peroxidase activity of the pap-Cu2Se experimental group increased to 138% of the original. This result not only confirmed the promoting effect of laser irradiation on enzyme activity, but also highlighted the potential application value of pap-Cu2Se composite materials in enhancing peroxidase activity.
[0065] Figure 4 This is a transmission electron micrograph of the enzyme composite catalyst after modification of the material. In the characterization analysis of transmission electron microscopy (TEM), we conducted a 2-x The TEM images clearly show the uniform dispersion of cuprous selenide nanoparticles at a scale of 100 nm. These nanoparticles exhibit uniform size and shape, indicating the precise control of the size and morphology of the nanoparticles during the synthesis process. At the same time, the TEM images show that the cuprous selenide nanoparticles are uniformly dispersed on papain (Pap), which indicates that the cuprous selenide nanoparticles are successfully loaded on papain.
[0066] In summary, the present invention proposes a nanozyme-natural enzyme coupling catalyst regulated by near-infrared light in the second region, which realizes photoenzyme coupling at a microscopic perspective by in situ growing copper sulfide quantum dots on the natural enzyme and utilizing the LSPR effect of copper sulfide nanoparticles.
[0067] The above-mentioned embodiments merely express several implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it should not be understood as limiting the scope of the present invention.
Claims
1. A method for preparing an enzyme-coupled catalyst regulated by near-infrared light in the second region, characterized in that: The method comprises the following steps: (1) dispersing the natural enzyme in ultrapure water to obtain an enzyme solution for later use; (2) After adding the CuCl2 solution to the enzyme solution, continue to add ultrapure water, and then stir to evenly disperse the copper source in the enzyme solution to obtain a mixed system for standby use; (3) The sodium borohydride solution and the sulfide salt solution are fully mixed and reacted vigorously and fully. When the color of the reaction system becomes transparent, a reaction solution A is obtained and set aside; (4) adding the reaction solution A of step (3) to the mixed system of step (4) and mixing thoroughly, the reaction system rapidly changes from transparent and colorless to reddish brown, and the reaction system gradually changes from reddish brown to dark green, the reaction is complete, and a reaction solution B is obtained for standby use; (5) transferring the reaction solution B into a dialysis bag and purifying the reaction solution B; (6) After purification, the reaction solution B was transferred to a freeze dryer for freeze drying to obtain a dry dark green sample powder. The sample powder was stored in a refrigerator at -85 to -75°C for later use.
2. The method according to claim 1, characterized in that In the step (1), the material-liquid ratio of the natural enzyme to ultrapure water is 8-12 mg:1 mL.
3. The method according to claim 1, characterized in that The concentration of the CuCl2 solution in step (2) is 0.01-0.03M, the amount of ultrapure water added accounts for 30-40% of the amount of ultrapure water in step (1), and the stirring speed is 850-950rpm.
4. The method according to claim 1, characterized in that: The concentration of the sodium borohydride solution in step (3) is 0.5-0.7M, and the concentration of the sulfide salt solution is 0.08-0.12M.
5. The method according to claim 1, characterized in that The molecular weight cutoff value of the dialysis bag in step (5) is 3200-3700Da. The purification is specifically to transfer the solution to the dialysis bag and then dialyze it 10 times with deionized water to remove excess impurities and ions in the solution.
6. The method according to claim 1, characterized in that The natural enzyme is one of a hydrolase, a protease or an oxidoreductase.
7. The method according to claim 1, characterized in that The chalcogenide salt solution is a solution prepared from oxides and salts of relevant chalcogenide elements.